Analysis of the implementation of the level of basic skills for emotional intelligence operations supervisors. Case: Pepsi-Cola C.A. Venezuela, Valencia Plant (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
This research has the purpose of analyzing the level of implementation of the core competencies of emotional intelligence monitors operations of the company Pepsi-Cola Venezuela CA Valencia plant to develop strategic proposals to close gaps and improve the climate in this way labor relation supervised and leveraging the strategic objectives of the organization. For the measurement was taken the instrument developed by Robert Cooper and Ayman Sawaf (2008) to objectively measure the level of development of each of the core competencies of emotional intelligence. Results from the instrument were analyzed using matrix DOFA from which they were drafted proposals to be considered by the company to ensure the optimum performance of the operations. The investigation and a descriptive study of field applied to a sample made up of finite monitors operations of the company in question. The main finding of the research is focused on providing the company with respect to a reference point for his team Supervisory opportunity to guide their strategies, which include training, competency assessment and feedback to achieve substantial improvements in leadership , Communication, organizational climate, motivation, continuous improvement, among others
Keywords: emotional intelligence; emotional competencies; leadership; competitive strategy